Hydrodynamic considerations on optimal design of a three-phase airlift bioreactor with high solids loading - Klein, Jaroslav (2003)
The hydrodynamic study of a three-phase airlift (TPAL) bioreactor with an enlarged gas–liquid dual separator was carried out. Different lengths and diameters of the draft tube were tested to show how the design of the separator zone affects the hydrodynamic performance of the TPAL reactor. Ca-alginate beads with entrapped yeast biomass at different loadings (0, 7, 14 and 21% v/v) were used in order to mimic the solid phase of conventional high cell density systems, such as those with cells immobilized on carriers or flocculating cells. Important information on multiphase flow and distribution of gas and solid phases in the internal-loop airlift reactor (ALR) with high solids loading was obtained, which can be used for suggesting optimal hydrodynamic conditions in a TPAL bioreactor with high solids loading. It is finally suggested that the ALR with a dual separator and a downcomer to riser cross-sectional area ratio (AD/AR) ranging from 1.2 to 2.0 can be successfully applied to batch/continuous high cell density systems, where the uniform distribution of solid phase, its efficient separation of particles from the liquid phase, and an improved residence time of air bubbles inside the reactor are desirable.